2022
DOI: 10.1021/acs.molpharmaceut.2c00549
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Fenofibrate as Oxidation-Sensitive Nanoparticles with ROS Scavenging and PPARα-Activating Bioactivity to Ameliorate Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in western countries and China. Fenofibrate (FNB) can activate peroxisome proliferator-activated receptor α (PPARα) to increase fatty acid oxidation and ameliorate NAFLD. However, the application of FNB is limited in clinic due to its poor water solubility and low oral bioavailability. In this study, FNB-loaded nanoparticles (FNB-NP) based on a reactive oxygen species (ROS)-responsive peroxalate ester derived from vitamin E (OVE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Moreover, a double-blind clinical trial performed on subjects with NAFLD demonstrated a reduction in serum triglyceride levels but also detected an increase in liver fat content [ 181 ]. Various researchers have tried to modify the chemical characteristics of fenofibrate, in particular using nanoparticles [ 182 , 183 ], obtaining good results in mouse models of NAFLD, with an important reduction in liver lipid concentration and oxidative stress [ 182 , 183 ]. Another activator of PPARα is pemafibrate, which has been recently evaluated in a large double-blind, randomized trial for its ability to reduce cardiovascular risk; although it was able to reduce plasmatic triglycerides and VLDL cholesterol, there was no difference in the number of cardiovascular events in the treated group that, however, showed a higher frequency of adverse renal events.…”
Section: Possible Therapeutic Approachesmentioning
confidence: 99%
“…Moreover, a double-blind clinical trial performed on subjects with NAFLD demonstrated a reduction in serum triglyceride levels but also detected an increase in liver fat content [ 181 ]. Various researchers have tried to modify the chemical characteristics of fenofibrate, in particular using nanoparticles [ 182 , 183 ], obtaining good results in mouse models of NAFLD, with an important reduction in liver lipid concentration and oxidative stress [ 182 , 183 ]. Another activator of PPARα is pemafibrate, which has been recently evaluated in a large double-blind, randomized trial for its ability to reduce cardiovascular risk; although it was able to reduce plasmatic triglycerides and VLDL cholesterol, there was no difference in the number of cardiovascular events in the treated group that, however, showed a higher frequency of adverse renal events.…”
Section: Possible Therapeutic Approachesmentioning
confidence: 99%